2007
DOI: 10.1111/j.1471-0528.2007.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in Yunnan, China: recent trends and associated factors

Abstract: Objective Yunnan Province, located in southwest China, is one of the poorest province in China. The maternal mortality ratio (MMR) is about twice the national average (56.2/100 000 live births), and in remote mountainous regions, the rate is five times higher. This study aimed to examine the progress in reduction of maternal mortality in the 1990s and early 2000s and the factors associated with this reduction in Yunnan.Design A population-based, longitudinal, ecological correlation study.Setting A remote provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 17 publications
5
43
0
Order By: Relevance
“…There is an association between illiteracy and the choice of hospital delivery found in one study in Yunnan province of China [16] , which is consistent with our findings. However, in our analysis the male illiteracy is the significant factor; it could be explained by gender inequity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There is an association between illiteracy and the choice of hospital delivery found in one study in Yunnan province of China [16] , which is consistent with our findings. However, in our analysis the male illiteracy is the significant factor; it could be explained by gender inequity.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the reduction in maternal mortality is strongly associated with socio-economic development in China and our findings confirm this in Guizhou province [9,[16][17][18] . The GDP of non-minority counties was three times more than that of minority counties in Guizhou, and this gap is increasing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings concur with previous analyses suggesting that China is making substantial progress towards achieving the target of 75% reduction in MMR by 2015. 4,[7][8][9]19 The observed annual decline of 6% is above the 5% required to reach the MDG5 target. 5 The pace of decline in maternal mortality was greatest in the poorest rural type-IV and most developed rural type-I counties, where the MMR fell by 10-11% per year.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,18 How these reforms have affected access to maternal health services and maternal mortality is not well known, and there is substantial evidence that rural areas remain marginalized, and that geographical inequalities persist. 7,9,10,19 A recent study based on the National Maternal and Child Health Reporting System (NMCHRS) reported a 5% annual decline in the MMR between 2000 and 2005 in all three geographic regions in China, and indicated no evidence of a widening disparity between them. 7 However, China's geographic regions represent only a very crude socio-economic stratification of the country, and using provincial-level data did not allow disaggregation of urban and rural variation.…”
Section: Introductionmentioning
confidence: 99%